2020
DOI: 10.3389/fmicb.2020.01459
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Optimizes Metabolism After Addition of Acyl-Homoserine Lactone Under Anaerobic Conditions

Abstract: Acyl-homoserine lactones (AHLs) are quorum sensing (QS) signaling molecules that mediate cell-to-cell communication in Gram-negative bacteria. Salmonella does not produce AHL, however, it can recognize AHLs produced by other species through SdiA protein modulating important cellular functions. In this work, the influence of the N -dodecanoyl-DL-homoserine lactone (C12-HSL) on glucose consumption, metabolic profile, and gene expression of Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…However, at the population level, the maintenance of bacterial metabolic homeostasis is important for energy conservation and resource utilization [23]. Recent reports have detailed the role of AHL-mediated QS in controlling nutrient intake and aiding in maintaining primary metabolism homeostasis in Burkholderia glumae [24], Pseudomonas aeruginosa [23], and Yersinia pestis [25]. Here, we propose a new mechanism for the regulation of cell metabolism mediated by the AI-2 QS systems.…”
Section: Discussionmentioning
confidence: 93%
“…However, at the population level, the maintenance of bacterial metabolic homeostasis is important for energy conservation and resource utilization [23]. Recent reports have detailed the role of AHL-mediated QS in controlling nutrient intake and aiding in maintaining primary metabolism homeostasis in Burkholderia glumae [24], Pseudomonas aeruginosa [23], and Yersinia pestis [25]. Here, we propose a new mechanism for the regulation of cell metabolism mediated by the AI-2 QS systems.…”
Section: Discussionmentioning
confidence: 93%
“…7 , first panel. A high concentration of signaling molecules would suggest an overcrowded environment, so organisms can adapt and reduce their metabolism for a possible substrate shortage ( 53 ). PICRUSt2 predicts possible functions of a community and must not be taken as a proof of actual metabolic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, amplification of SdiA can enhance resistance to mitomycin C by increasing the ability of chromosome replication and repair. Carneiro et al (2020) examined the expression of SdiA and genes associated with the nucleotide salvage pathway in Salmonella by qRT-PCR and found that SdiA affects glucose consumption, metabolism and gene expression in Salmonella and is closely related to metabolic pathways associated with glycine, purine, amino acid and aminoacyl tRNA biosynthesis. It plays a role in metabolic optimization under a high population density of Salmonella.…”
Section: Discussionmentioning
confidence: 99%